Factors affecting compliance behavior of multi drugs resistant tuberculosis patients at National Tuberculosis Centre, Nepal. - Maharjan,Bina (2011)
ABSTRACT: Background: Resistance to mycobacterium tuberculosis to anti tuberculosis drugs has emerged a major public health threat. Non compliance of MDR TB (Multi Drug Resistance Tuberculosis) patients to DOTS PLUS (Directly Observed Treatment Short Course) therapy results in XDR TB (Extreme Drug Resistance Tuberculosis) which could create havoc in public health. Thus, the objective of this study was to explore the compliance behavior and factors affecting compliance behavior among MDR TB patients. Methods: A descriptive cross-sectional study was carried out at National Tuberculosis Centre from 6th -30th March, 2011. A total of 60 patients were included in the study that had been registered as MDR TB patients in National Tuberculosis Centre and had been on treatment for three months or more. Data was collected by face to face interview using structured questionnaire. Results: Adequate compliance behavior was exhibited by 96.67% respondents irrespective of age, sex, religion, ethnicity, educational status and occupation. It was obsevered that majority of the respondents were category II smear failures. Majority (70%) had the history of anti tuberculosis medicine. Most of the respondents considered TB as the communicable disease and 76.7% knew that TB is transmitted through droplets. Only 20% respondents knew that bacteria caused TB. About 56.7% respondents had knowledge about MDR TB out of which 28.3% had correct knowledge i.e. TB resistance to first line anti-tuberculosis medicine. In this study 50% of the respondents had easy access to the DOTS PLUS sub centre while 50% didn't have easy access to the sub centers. Almost all the respondent considered the behavior of the health worker to be good. The average expense required for the respondent related just for the treatment process was Rs. 300 per day. There was strong association between educational status and knowledge about MDR TB (p value 0.000). There was significant relationship between educational status and knowledge about symptoms (p value 0.029). There was strong association between educational status and knowledge about consequences of discontinuation (p value 0.000). Conclusions: Adequate compliance behavior was exhibited by 96.67% respondents irrespective of age, sex, religion, ethnicity, educational status and occupation. Key words: TB, MDR TB, compliance behavior, DOTS PLUS